Quantum Oscillations in Ferromagnetic (Sb, V)2Te3 Topological Insulator Thin Films. Issue 41 (31st August 2021) - Zhang, Liguo; Helm, Toni; Lin, Haicheng; Fan, Fengren; Le, Congcong; Sun, Yan; Markou, Anastasios; Felser, Claudia
Abstract: An effective way of manipulating 2D surface states in magnetic topological insulators may open a new route for quantum technologies based on the quantum anomalous Hall effect. The doping‐dependent evolution of the electronic band structure in the topological insulator Sb2− x V x Te3 (0 ≤  x  ≤ 0.102) thin films is studied by means of electrical transport. Sb2− x V x Te3 thin films were prepared by molecular beam epitaxy, and Shubnikov–de Hass (SdH) oscillations are observed in both the longitudinal and transverse transport channels. Doping with the 3d element, vanadium, induces long‐range ferromagnetic order with enhanced SdH oscillation amplitudes. The doping effect is systematically studied in various films depending on thickness and bottom gate voltage. The angle‐dependence of the SdH oscillations reveals their 2D nature, linking them to topological surface states as their origin. Furthermore, it is shown that vanadium doping can efficiently modify the band structure. The tunability by doping and the coexistence of the surface states with ferromagnetism render Sb2− x V x Te3 thin films a promising platform for energy band engineering. In this way, topological quantum states may be manipulated to crossover from quantum Hall effect to quantum anomalous Hall effect, which opens an alternative route for the design of quantum electronics and spintronics. Abstract : A systematic study of electric transport in Sb2− x V x Te3 films demonstrates the coexistence of topological surface states and long‐range ferromagnetism evidenced by Shubnikov–de Haas oscillations. Vanadium doping acts as an efficient tuning parameter for the Fermi surface size. This opens up a new route for the investigation of the crossover between different topological states based on this material class.